From gift to gibt: Drifts and links between Donner le temps I and II - da Lowry, Santiago Cane (Escritura e Imagen, 2023)
This paper wants to bring up some perspectives and key points in a reading of the first part of Derrida’s seminar Donner le temps, published in 1991, in the wake of the publication of its second part, in 2021, unpublished till then and long awaited for its readers. It doesn’t build bridges, so to speak, between parts, but it takes on the aporetics of Derrida’s formulation on the gift in the first part of the seminar, as an invitation to read it again but framed within a sort of reactivation of the interest in this seminar, now complete, as well as a more specific approach to the complexities involved in deconstructive work and the role that, in both questions, plays the notions of future (as it is the common translation of french avenir) and impossibility. Also, it plans to draw attention to Derrida’s strategies in coping with the aporias of gift, sketching its relations to forgiveness, always in the trace of the deconstructive effects caused by the, sort of equalization, of possibility and impossibility in Derrida’s comprehension of future (avenir).